Genetically predicted circulating levels of cytokines and the risk of osteoarthritis: A mendelian randomization study - Su, Dalin; Ai, Yanhong; Zhu, Guoyong; Yang, Yubiao; Ma, Pengyi (Frontiers in Genetics, 2023)
Background: The association between inflammatory cytokines and osteoarthritis (OA) has been reported in several observational studies, but the causal relationship between these two remains unknown. Hence, we performed this two-sample Mendelian randomization (MR) to confirm the causal relationship between circulating levels of inflammatory factors and osteoarthritis risk. Method: We used genetic variants associated with cytokine circulation levels from a meta-analysis of genome-wide association studies (GWASs) in 8,293 Finns as instrumental variables and obtained OA data from the United Kingdom Biobank, including a total of 345,169 subjects of European ancestry (66,031 diagnosed OA cases and 279,138 controls). Inverse variance weighting (IVW), MR-Egger, Wald Ratio, weighted median, and MR multiplicity residual sums with outliers (MR-PRESSO) were used. Result: We found a causal relationship between circulating levels of macrophage inflammatory protein-1beta (MIP-1β) and risk of OA (OR = 0.998, 95% CI = 0.996–0.999p = 9.61 × 10−5); tumour necrosis factor beta (TNF-β) was also causally associated with risk of OA (OR = 0.996,95%CI = 0.994–0.999, p = 0.002); finally we found a suggestive association between C-C motif chemokine ligand 5(CCL5, also called Rantes) and OA risk (OR = 1.013, 95%CI = 1.002–1.024,p = 0.016). Conclusion: Our findings offer promising leads for the development of new therapeutic targets in the treatment of osteoarthritis. By identifying the role of inflammatory cytokines in this debilitating condition through a genetic epidemiological approach, our study contributes to a better understanding of the underlying disease mechanisms. These insights may ultimately pave the way for more effective treatments that improve patient outcomes.